Miller, J.F., Strauss Clay, J. (eds.) (2019). Tracking Hermes, Pursuing Mercury - Allan, Arlene (ARYS. Antigüedad: Religiones y Sociedades, 2020)
MILLER, JOHN F. and STRAUSS CLAY, JENNY (eds.) (2019). Tracking Hermes, Pursuing Mercury. Oxford: Oxford University Press. 416 pp., 90,17€ [ISBN  978- 0-1987-7734-2] [Book review]